A Survey of the Medical Needs of a Group of Small Factories. Issue 3 (July 1962) - Lee, W. R.
Abstract : The present interest in medical services for small factories is matched by the limited objective information which is available on the demand for and needs of such services. As a teaching project, a survey was made of factories with between 30 and 200 employees on an estate in the North West where there was no organized medical service. Unfortunately, time allowed only 22 factories to be visited. The findings, therefore, are regarded as indicative rather than conclusive, but this does not detract from their interest. Factories were visited by two or three postgraduate students who completed a questionnaire designed to standardize their findings. The questionnaire is included as an appendix to this paper. Regarding the demand for medical services, four of the 22 factories were subsidiaries of larger organizations and had part-time medical advice, 14 expressed no interest even if this would have involved no financial commitment, and the remaining four were interested for differing reasons. The needs of the factories in this context were found to be, first, advice and perhaps better supervision of non-mechanical hazards and, secondly, supervision of the first aid arrangements. From the ambulance journey records of the local authority there appeared to be no great demand for local casualty facilities. To meet these needs it is suggested that the functions of the appointed factory doctor might be modified to include wider supervision of non-mechanical hazards and supervision of first aid arrangements. It is also suggested that the National Health Service should form the basis for dealing with those cases requiring more than first aid.